Espaços vetoriais e topológicos de intervalos generalizados com alguns conceitos de cálculo e otimização intervalar - Costa, Tiago Mendonça da [UNESP] (2014)
This work presents a method to endow the generalized interval set M = I(R) ∪ I(R); where I(R) = f[a1; a2] : a1 a2 and a1; a2 2 Rg and I(R) = f[a1; a2] : [a2; a1] 2 I(R)g; with some different structures, such as algebraic, topological, and metric. We also equip M with order relations. Actually, we did this in a more general context because we worked in Mn = M M M for n 2 N: We formulated interval optimization problems and related them to classic multi-objective optimization problems. We presented a version of the mini-max Theorem in the interval context, and also developed concepts of calculus on the generalized interval space which are used to find the attainable state set of a classic differential inclusion under some given conditions